2010
DOI: 10.1007/s00441-010-0985-5
|View full text |Cite
|
Sign up to set email alerts
|

Differential apoptosis-like cell death in amastigote and trypomastigote forms from Trypanosoma cruzi-infected heart cells in vitro

Abstract: Apoptosis, type-I of programmed cell death (PCD-I), is not restricted to multicellular organisms since many apoptotic features have been described in different trypanosomatids, including Trypanosoma cruzi. Our present aim was to monitor, by different morphological markers, the occurrence of apoptosis-like death in amastigotes and trypomastigotes of T.cruzi (Y strain) during the infection of heart culture cells. We documented the differential occurrence of PCD-I in amastigotes and trypomastigotes, with distinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 50 publications
2
20
1
Order By: Relevance
“…Apoptosis-like death has been reported in T. cruzi amastigote nests and trypomastigotes, and hypothesized to be the result of control of parasite burden regulated by the parasite itself or by the host, parasite evasion of the host immune response and clonal selection [13],[38][39]. However, these studies were conducted during the acute phase [13],[38], whereas we observed apoptosis-like death in nests during both the acute and chronic phases.…”
Section: Discussioncontrasting
confidence: 54%
“…Apoptosis-like death has been reported in T. cruzi amastigote nests and trypomastigotes, and hypothesized to be the result of control of parasite burden regulated by the parasite itself or by the host, parasite evasion of the host immune response and clonal selection [13],[38][39]. However, these studies were conducted during the acute phase [13],[38], whereas we observed apoptosis-like death in nests during both the acute and chronic phases.…”
Section: Discussioncontrasting
confidence: 54%
“…Still, cardiomyocytes infected with T. cruzi clone Dm28c have higher levels of apoptosis compared to infection with strains Y and CL (de Souza et al, 2003). Furthermore, the intracellular parasites themselves also undergo apoptosis, hinting at a host attempt to control parasite burden (de Souza et al, 2003, 2010). Interestingly, it has been shown that α2-macroglobulin, a plasma proteinase inhibitor, regulates apoptosis in T. cruzi -infected cardiomyocytes and macrophages, impairing the cell death process (de Souza et al, 2008).…”
Section: Effect Of T Cruzi Infection In Cardiomyocyte Physiologymentioning
confidence: 99%
“…After 48 h induction with TMP-lactate the majority of amastigotes expressing these fusion proteins stained positive, indicating that apoptosis-like cell death in amastigotes occurred with the expression of all these proteins. It has been reported that T. cruzi could undergo apoptosis-like cell death [37,38]. However, the pathways leading to apoptosis-like cell death in this organism require further explorations.…”
Section: Discussionmentioning
confidence: 99%